2020
DOI: 10.17352/aest.000021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insecticide residues in cabbage (Brassica oleracea var. Capitata) from three major markets in Kumasi

Abstract: Cabbage from 3 major markets (Abinchi, Bantama and Sofoline) in Kumasi were screened for organochlorine, organophosphate and pyrethroid insecticide residues. Ninety cabbage heads-30 from each market-were randomly sampled and analysed at the Pesticide Residues Laboratories of the Ghana Standards Authority, Accra. The analysis was carried out using Multiple Reaction Monitoring by Gas Chromatography-Pulsed Flame Photometric Detector (GC-PFPD), Gas Chromatography-Electron Capture Detector (GC-ECD) and Quick, Easy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This may be an indication that DDT and its metabolites were not used in cabbage farming from those sampling areas. Apart from that, those pesticides may be below their limit of detection, which is consistent with a study from Ghana [ 43 ]. However, the result of this study was against the study done in Senegal and Tanzania, which reported the most critical commodity with multiple existences of pesticides including DDT and its metabolites were cabbage [ 8 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…This may be an indication that DDT and its metabolites were not used in cabbage farming from those sampling areas. Apart from that, those pesticides may be below their limit of detection, which is consistent with a study from Ghana [ 43 ]. However, the result of this study was against the study done in Senegal and Tanzania, which reported the most critical commodity with multiple existences of pesticides including DDT and its metabolites were cabbage [ 8 , 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…The immediate response by the rural farmers was the use of the chemical pesticides from hazardous origins. Knowing the negative impact of the chemical pesticides on the environment and human health (Assogba-Komlan et al, 2007;Agboyi et al, 2015;Ngom et al, 2012;Otchere et al, 2020), along with the development of resistance in the pest and the non-target effects (Yehouenou et al, 2006), there was an urgent need to search fora sustainable and ecofriendly solution for the management of the FAW on maize. This study was embedded in the national research program in Togo, West Africa, to implement eco-friendly strategies for control of the FAW on maize.…”
Section: Introductionmentioning
confidence: 99%